Análisis comparativo del manejo tradicional y técnico del cultivo de setas (pleurotus ostreatus), en la comunidad pacto sumaco, parroquia jatun sumaco, cantón archidona - Quevedo Castillo, Lidia Elizabeth (2016)
In the research called Comparative Analysis of Traditional and Technical Management of Mushroom Cultivation (Pleurotus ostreatus), in the Pacto Sumaco community, Jatun Sumaco Parish, Archidona Canton; The following objectives were set: To carry out a diagnosis of the oyster mushroom production system implemented to date in "Sumac Pacto", Implement a culture of oyster mushrooms (Pleurotus ostreatus) in a technified form and compare the productive and economic process with the traditional system , Socialize the results with the community Pact Sumaco of the canton Archidona, province of Napo. In the methodology the scientific, analytical and descriptive method was used in conjunction with the techniques of direct observation, survey and day of field. The elements of study were: situational diagnosis of production systems and profitability. As results we have that the main economic activity of the Pacto Sumaco community is agriculture 67% of the respondents consider that it is profitable, having the naranjilla with 47% and the oyster mushrooms with 40%, as the most important crops. 63% of the mushroom production is sold to the city markets and 31% to the visitors, 93% of the producers consider this production profitable, however 93% state that they do not know exactly the investment And the profit obtained in production. The traditional management of the mushroom cultivation reached a yield of 9 mushrooms per substrate sheath with an average weight of 56.7g c / u. Giving a total crop yield of 259.6 pounds, in a space of 18 obtaining a utility of $ 182.00, while the technical management achieved a yield of 14 mushrooms per substrate sheath with an average weight of 56.7g c / u. Giving a total crop yield of 411.2 pounds, in a space of 18 obtaining a profit of $ 408.20. The socialization of the results of the profitability of mushroom cultivation was given to all the producers involved. It was obtained a great reception and different contributions to the subject which were motivated to apply the techniques of this research work and to improve the results of its production of mushrooms. It can be concluded that the production of mushrooms in the technical management achieved higher economic yield was obtained 411.2 pounds with a profitability of 65% compared to the traditional management that obtained 259.6 pounds with a profit of $ 182.00, with a profitability of 38% That the profitability of the technical management surpassed with 27% to the traditional management. It is recommended to apply the techniques of direct observation, use of materials, laboratory equipment, asepsis in a correct way and constant monitoring to the pockets of the crop to prevent possible contaminations as this reflects losses for the producer.